Maize growth and temperature in the Kenya highlands - Hawkins, Richard (1979)
Field experiments were conducted at Kitale, Kenya to investigate the effects of early soil warming on growth and yield of Zea mays. In the first of these experiments (1976) a polythene mulch was applied to warm the soil of late planted maize. In the second experiment (1971) maize with a mulch was planted at three intervals after the start of the rainy season. These two experiments showed that warming soils by 5 - 6°C caused a small increase (1 - 2) in number of leaves initiated, but early leaves were smaller and thus total leaf area produced was unaffected. Spikelet initiation began 2 - 3 weeks after the apical meristem emerged above ground level, and as the embryonic cobs were in the aerial environment; soil warming did not affect the number of spikelets initiated. The grain number at harvest, which was the major variable of the yield components, was found to be determined by the survival rate of initiated spikelets. A subsidiary trial, involving the use of different plant populations, showed similar numbers of spikelets initiated by plants of different size and growth rate. The field experiments also showed that plant size at any stage is not a discriminant of yield, but a good relationship was found between growth rate during the 'linear' phase of growth and final grain number. A decrease of 30 % crop growth in late planted maize (1977) was associated with a decrease in mean early soil temperature of 0.7°C. Controlled environment studies at Sutton Bonington, England, showed that an increase of early soil temperature (ca 6° C at the meristem depth) increased the photosynthesis rate of subsequent leaves by about 20 % but this increase is not consistent with changes in growth rate observed in field experiments at Kitale. These findings do not support the hypothesis that poor yields of late planted maize are a result of decreases in soil temperature. Previously discarded hypotheses based on the leaching of nutrients should be re-examined.